Monocytes as Potential Mediators of Pathogen‐Induced T‐Helper 17 Differentiation in Patients With Primary Sclerosing Cholangitis (PSC). Issue 4 (8th October 2020) - Kunzmann, Lilly Kristin; Schoknecht, Tanja; Poch, Tobias; Henze, Lara; Stein, Stephanie; Kriz, Marvin; Grewe, Ilka; Preti, Max; Hartl, Johannes; Pannicke, Nadine; Peiseler, Moritz; Sebode, Marcial; et al.
Abstract : Background and Aims: T cells from patients with primary sclerosing cholangitis (PSC) show a prominent interleukin (IL)‐17 response upon stimulation with bacteria or fungi, yet the reasons for this dominant T‐helper 17 (Th17) response in PSC are not clear. Here, we analyzed the potential role of monocytes in microbial recognition and in skewing the T‐cell response toward Th17. Approach and Results: Monocytes and T cells from blood and livers of PSC patients and controls were analyzed ex vivo and in vitro using transwell experiments with cholangiocytes. Cytokine production was measured using flow cytometry, enzyme‐linked immunosorbent assay, RNA in situ hybridization, and quantitative real‐time PCR. Genetic polymorphisms were obtained from ImmunoChip analysis. Following e x vivo stimulation with phorbol myristate acetate/ionomycin, PSC patients showed significantly increased numbers of IL‐17A–producing peripheral blood CD4 + T cells compared to PBC patients and healthy controls, indicating increased Th17 differentiation in vivo . Upon stimulation with microbes, monocytes from PSC patients produced significantly more IL‐1β and IL‐6, cytokines known to drive Th17 cell differentiation. Moreover, microbe‐activated monocytes induced the secretion of Th17 and monocyte‐recruiting chemokines chemokine (C‐C motif) ligand (CCL)‐20 and CCL‐2 in human primary cholangiocytes. In livers of patients with PSC cirrhosis, CD14 hi CD16 int and CD14 lo CD16 hi monocytes/macrophages were increased compared to alcoholic cirrhosis, and monocytes were found to be located around bile ducts. Conclusions: PSC patients show increased Th17 differentiation already in vivo . Microbe‐stimulated monocytes drive Th17 differentiation in vitro and induce cholangiocytes to produce chemokines mediating recruitment of Th17 cells and more monocytes into portal tracts. Taken together, these results point to a pathogenic role of monocytes in patients with PSC.